Characterization of Fusarium species associated with tobacco diseases in Northwestern Argentina - Berruezo, Lorena Andrea (2018)
Tobacco (Nicotiana tabacum L.) production is centred in the northwestern region of Argentina (NWA), where the incidence of root rot and stem diseases has increased considerably in recent years. This study aimed to analyse the genetic, morphological and pathogenic diversity of the Fusarium oxysporum and F. solani complexes (hereafter FOSC-FSSC), causing Fusarium wilt and root rot. One hundred tobacco fields were surveyed at six locations during two consecutive seasons, and 130 isolates were recovered from symptomatic tobacco plants. The isolates were characterized by morphological traits, molecular characteristics (EF1-α sequence) and pathogenicity tests. All of the isolates were identified as members of the FOSC or FSSC, exhibiting considerable intra-group variation. Three morphotypes were differentiated based on morphological characters in both complexes. The phylogenetic tree generated from the EF1-α sequences confirmed the isolates’ identification. The pathogenicity of the isolates towards tobacco seedlings was assessed in a greenhouse. Considerable variability in pathogenicity was observed among the isolates. Differences in the levels of pathogenicity were recorded. In the FOSC and FSSC, 81% and 60% of the isolates were pathogenic, respectively. In this study, members of FOSC and FSSC exhibited considerable variability in morphological characteristics and virulence, and a portion of them were non-pathogenic for tobacco. To the best of our knowledge, this study is the first to provide information on the variability of the pathogens associated with tobacco wilt and root rot in NWA. This work contributes to the development of sustainable management strategies in tobacco production.